Repeatability and comparability of peripapillary vessel density measurements of high-density and non-high-density optical coherence tomography angiography scans in normal and glaucoma eyes. Issue 7 (17th August 2018) - Venugopal, Jayasree P; Rao, Harsha Laxmana; Weinreb, Robert N; Dasari, Srilakshmi; Riyazuddin, Mohammed; Pradhan, Zia Sultan; Puttaiah, Narendra K; Devi, Sathi; Mansouri, Kaweh; Webers, Carroll A B
Abstract : Aims: To compare the peripapillary vessel density (VD) measurements of high-density (HD) and non-HD optical coherence tomography angiography (OCTA) scans in normal and glaucoma eyes, and to evaluate the intrasession repeatability of VD measurements of HD scans. Methods: In a cross-sectional study, 46 normal (33 subjects) and 89 glaucoma (64 patients) eyes underwent 3 HD and 1 non-HD optic nerve head OCTA scans in the same session. Agreement in VD measurements between HD and non-HD scans was assessed using Bland and Altman analysis. Repeatability of the VD measurements of HD scans was assessed using within-subject coefficient of repeatability (CRw) and variation (CVw). Results: The mean difference in the VDs ranged between 0.7% (temporal sector VD) and 2.0% (inferonasal sector VD), with HD scans showing significantly greater VD values than non-HD scans. The 95% limits of agreement (LoA) in glaucoma eyes ranged between −2.0% and 5.0% for whole enface VD and between −4.8% and 9.6% for superotemporal VD. CRw (%) and CVw (%) of VD measurements of HD scans ranged from 3.0 to 4.9 and from 2.0 to 3.1 in normal eyes. The same ranged from 3.2 to 6.7 and from 2.6 to 4.8, respectively, in glaucoma eyes. Conclusions: VD of HD scans was higher than that of non-HD scans. The wide 95% LoA indicates that the VD measurements of HD and non-HD scans cannot be used interchangeably. Test–retest repeatability of VDs on HD scans was as high as 6%. These results should be considered while using OCTA for longitudinal evaluation of glaucoma.